Mengamati Kehidupan Owa Jawa Dalam Penyutradaraan Film Dokumenter "Habitat" Dengan Bentuk Penuturan Perbandingan - Kawakibi Muttaqien; Dyah Arum Retnowati; Gregorius Arya Dhipayana (Sense: Journal of Film and Television Studies, 2019)
ABSTRACTDocumentary is one among many ways to tell a fact and information from surroundings. One of it are endemic animals called Javan Gibbon.This thesis documentary tells about Javan Gibbon who lives in three different habitat which are wild life, rehabilitation center and zoo. Different environment influences the daily activiy of each Javan Gibbon. For Javan Gibbon, jungle is their natural habitat. Rehabilitaion center is a place for them to be rehabilitate before being release to wild life. While zoo is a place for preservation and education for people.This thesis, Observing the Life of Javan Gibbon in Directing Documentary “Habitat” with Narrative Form of Comparison, contains the comparison of Javan Gibbon on three different habitats. The comparison is delivered with sequences of footages between each habitat through activities of Javan Gibbon. The activity consists of the process of getting food, socialize between each Gibbon, interacting with humans and during rainy seasons. keywords: documentary, javan gibbons habitat, comparison, directing ABSTRAKFilm dokumenter merupakan satu dari sekian banyak cara untuk menyampaikan sebuah fakta dan informasi dari apa yang terjadi di sekitar kita. Salah satunya adalah satwa endemik yaitu owa Jawa.Karya tugas akhir film dokumenter ini menceritakan tentang owa Jawa yang hidup di tiga habitat yaitu alam liar, penangkaran rehabilitasi dan kebun binatang. Lingkungan yang berbeda mempengaruhi pola kehidupan sehari-hari dari masing- masing owa Jawa. Bagi owa Jawa, hutan merupakan habitat alaminya. Penangkaran merupakan tempat rehabilitasi sebelum dikembalikan ke alam liar. Sedangkan kebun binatang merupakan tempat pelestarian dan sarana edukasi bagi masyarakat.Perbandingan owa Jawa ini dikemas dalam karya tugas akhir yang berjudul Mengamati Kehidupan Owa Jawa dalam Penyutradaraan Film Dokumenter “Habitat” dengan Bentuk Penuturan Perbandingan. Perbandingan ini disampaikan dengan menyajikan runtutan gambar antara habitat satu dengan habitat lainnya melalui kegiatan owa Jawa. Kegiatan tersebut meliputi proses mendapatkan makanan, bersosialisasi dengan sesama owa Jawa, berinteraksi dengan manusia, dan menghadapi kondisi cuaca seperti hujan. kata kunci: film dokumenter, habitat owa jawa, perbandingan, penyutradaraan